Phototrophic bacteria grown in palm oil mill effluent as feed for culturing rotifers and marble goby larvae / Loo Poh Leong - Loo, Poh Leong (2012)
The culture of the highly priced marble goby Oxyeleotris marmorata (Bleeker) in the Asian region is currently beset by the poor supply of fingerlings which are largely collected from the wild, while larviculture based on conventional feeds has not been producing enough due to high larval mortality. Phototrophic bacteria (PB), an unconventional feed has not been seriously considered as an alternative feed despite being nutrient-rich. Thus, the overall objective of this study was to evaluate the feasibility and success of culturing larval marble goby and rotifer (Brachionus rotundiformis) using a selected PB species grown in palm oil mill effluent (POME) as feed. The PB species tested were Rhodopseudomonas palustris, Rhodobacter sphaeroides and Rhodovulum sulfidophilum (PD1). Live feed (rotifers and Artemia nauplii) cultured from the settled biomass of PB produced in synthetic 112 medium could not support the survival of larval marble goby. Only live feed fed the biomass of POME-grown R. sulfidophilum (bPOME-PD1) supported good larval survival. Fatty acid analysis revealed that only bPOME-PD1 contained both docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). The study supports the hypothesis that PB grown in synthetic media lacks the essential fatty acids or/and their precursors that are crucial for larval fish survival. The effective use of bPOME-PD1 as a feed for marble goby larvae, given directly or indirectly (via live feed), has demonstrated that larvae fed directly could not achieve consistent survival, whereas those fed indirectly showed consistent and significantly higher (P<0.01) survival. It may be that bPOME-PD1 is not of optimal prey size or/and it contained unsuitable high ratio of DHA/EPA and ARA (arachidonic acid)/EPA. The batch culture of rotifers using unsettled POME-grown R. sulfidophilum culture (cPOME-PD1) supported even higher rotifer production (898 individuals/mL) as compared to bPOME-PD1 (323 individuals/mL) or just POME (533 individuals/mL). Fish larvae survived better in 5 ppt salinity as compared to 10 ppt iii salinity. The increase in stocking density from 10 to 15 larvae/L did not affect the larval survival and growth, but higher stocking density of 20 larvae/L and 30 larvae/L resulted in low survival and growth. Larvae cultured in grey coloured tanks and given live feed fed with cPOME-PD1 had the highest survival as compared to those cultured in black and transparent tanks. The findings did not totally accept the hypothesis that the dark coloured tank supports higher survival of marble goby larvae than light coloured tank. Further investigation using grey tanks demonstrated that live feed fed cPOME-PD1 or bPOME-PD1 were equally good in sustaining good larval fish survival (71.4 - 81.9%) and growth (11.07 - 12.30mm total length). Surviving larvae contained low ratios of DHA/EPA (3 - 4) and ARA/EPA (0.1 - 2) as compared to larvae fed bPOME-PD1 or microalgae (Nannochloropsis sp.) which contained high ratios of DHA/EPA (>11) and ARA/EPA (>5). The optimal conditions for marble goby production are grey tank, 5 ppt salinity, larval stocking density of 15/L and live feed fed POME-PD1 to give DHA:EPA:ARA ratio of approximately 7:2:1. A stable marble goby larviculture with viable commercial production has resulted from this study.